THE TEACHINGS OF AL-GAZALI'S RELIGIOUS TOLERANCE AND MODERATION (An Examination of Al-Gazali's Thoughts on Faith and Infidelity in the Book of Fasl Al-Tafriqah Bayna Al-Islam Wa Al-Zandaqah) - Rahmat; Soleh, Achmad Khudori (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to analyze and understand Al-Gazali's teachings on religious tolerance and moderation through his views on faith and unbelief as contained in his work, Fasl Al-Tafriqah Bayna Al-Islam Wa Al-Zandaqah. This research is qualitative research with a text analysis approach. The data sources in this study consist of primary and secondary data, data collection techniques using library research and text analysis, data analysis using content analysis and contextual interpretation, and data validity consisting of source triangulation and source criticism. The results of the study show that Al-Ghazali's teachings on religious tolerance and moderation, as described in Fasl al-Tafriqah bayna al-Islam wa al-Zandaqah, offer a view that rejects extremism in assessing a person's faith, while emphasizing the importance of a fair and moderate approach. Al-Ghazali asserts that the assessment of an individual's faith is the exclusive right of God, not humans. Al-Ghazali teaches that a person's beliefs should not be used as a reason to justify discrimination or violence. Al-Ghazali's teachings on tolerance and moderation are not only relevant in the context of Islamic history but also serve as a universal guide. This study is expected to contribute academically by adding to the wealth of literature related to Al-Ghazali's thoughts on religious tolerance and moderation, while also broadening our understanding of the concepts of faith and disbelief according to his views. Keywords: Al-Ghazali's thoughts, Tolerance, Moderation, Faith, Disbelief